Construction mechanism for service path over reconfigurable service-centric network - Dan ZHAO; Feng WEN; Xin XU; Peng WANG; Bo CHEN (Tongxin xuebao)
In order to enhance the flexible and intelligent network's service ability,a novel architecture called recon-figurable service-centric network (ReSCNet) was proposed which decomposed traditional network capabilities and ser-vices into fine-grained network functional unit.Then based on service routing matrix algorithm to orchestrate and deploy atomic service flexibly,a service path was built which possess smaller cost,lower time delay,higher degree of load bal-ance and higher reliability.Finally,the performance of service routing matrix algorithm was evaluated on the innovation experiment platform NetFPGA-10G.The simulation results show that the algorithm has a better performance and can cus-tomize an optimal service path for users while meet the specific functions and performance constraints.